PP-US: An Optimized Ultrasonic Sensor Module for Intelligent Parking in Three-Dimensional Garages - Yu Chuan Jiang; Fang Quan Yang (Tehnički Vjesnik, 2025)
Urban parking challenges are exacerbated by the increase in car ownership, which requires innovative solutions. This study presents a novel Parking Path-Ultrasonic Sensor (PP-US) start stop module for intelligent vehicle parking in three-dimensional garages. The system integrates ultrasonic sensors with a fuzzy control algorithm to optimize parking path planning and execution. Experimental results demonstrated the excellent performance of the module, with a response time of 30 ms after 140 iterations, significantly outperforming existing frameworks. The PP-US module achieved high accuracy in distance measurement, with errors ranging from 0.01 to 0.04 m within 0.5-2.4 m. In parking tests, the system maintained stable vehicle speed between 3-5 km/h, and demonstrated smooth trajectory control. The comprehensive anti-interference ability score of this module was 0.91, surpassing comparison systems. These findings highlight the potential of the PP-US module in enhancing parking efficiency and safety in complex three-dimensional garage environments.